PO 54 - HIGH-FREQUENCY OSCILLATORY VENTILATION IN A NEONATE WITH CONGENITAL DIAPHRAGMATIC HERNIA FOR VATS - Saldanha Marques, João; Tavares, Francisca; Araújo, Rosa (Journal of the Portuguese Society of Anesthesiology, 2023)
x